Carbon nanotube‐deposited layer on cathodic catalyst layer in polymer electrolyte membrane fuel cell for enhanced performance in low humidity condition. (5th August 2022) - Jeong, Seokhun; Kwon, Obeen; Kim, Jaeyeon; Yoo, Hongnyoung; Cha, Hyeonjin; Choi, Heesoo; Kim, Hyeok; So, Younho; Park, Taehyun
Summary: An ultrathin layer composed of carbon nanotubes (CNTs) was deposited on the cathodic catalyst layer to boost performance of polymer electrolyte membrane fuel cell (PEMFC) under low to mid relative humidity (RH) conditions. The CNT‐deposited layer (CDL) was formed without modifying the PEMFC components. To investigate the behavior of water and reactants at the inner interface of the membrane electrode assembly (MEA), we characterized the morphology of the CDL (contact angle, pore size distribution, specific surface area, field emission scanning electron microscopy, and energy dispersive spectroscopy images). The CDL in PEMFCs was used as a contributor to enhance the membrane hydration. Thereby performances have been significantly enhanced. Additionally, the three‐dimensional nanostructure of the CDL expanded the active area by uniform dispersion of the reactants. The polarization curves of the conventional MEA and MEA with CDL were evaluated under diverse RH (100%, 70%, 50%, and 30% RH). In the low to mid RH conditions, the maximum power densities were increased by 29.7% (70% RH), 26.6% (50% RH), and 25.5% (30% RH) compared with the conventional MEA. Especially, the maximum power density of the MEA with CDL (0.547 W/cm 2 at 70% RH) was higher than that of the conventional MEA (0.482 W/cm 2 at 100% RH). Thus, MEA with CDL demonstrated excellent performance enhancement under low to mid RH conditions.